Potential of endophytic bacteria as producers of antibiotics: A literature review - Scania, Alifah Evi; Ibrahim, Fera (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2024)
Microbial infection is a significant contributing aspect to the development of diseases, posing ongoing challenges in - healthcare. Numerous synthetic antibiotic agents have been used as therapeutic interventions; however, many microorganisms exhibit resistance to these synthetic agents. The rate at which microbes developed resistance to antibiotics has outpaced the discoveries and study of new treatments. The potential of endophytic bacteria to produce bioactive compounds or metabolites that can serve as the basis for developing new antibiotic drugs is promising is promising. This review aims to explore the metabolite potential of endophytic bacteria as a source of antibiotics. Understanding the mechanism and potential of endophytic bacteria offers opportunities for the advancing therapeutic interventions to mitigate the negative effects of various strains of antibiotic-resistant pathogenic bacteria.